Physiological and physical seed dormancy of some hypericum species growing in Turkey. - Çırak, Cüneyt; Ayan, Ali Kemal; Kevseroğlu, Kudret (Plant Breeding and Seed Science, 2006)
To investigate the nature of dormancy in Hypericum androsaemum, H. scabrum, H. lydum and H. tetrapterum seeds which did not show germination under nor mal laboratory conditions. The 15 day long germination experiment under the constant light pre ceded by 30 min soaking in water (tap water, 40, 50 and 60°C hot water), GA3 (50, 100 and 150 ppm) and H2SO4 (1, 2 and 3%) was per formed. The germination response to the pre-soaking treatments was variable and discussed as a possible result of double dormancy involving partially dormant embryo and a chemical inhibitor for H. androsaemum and H. scabrum. Seed germination was restricted only by hard seed coat in H. lydum, and H. tetrapterum indicating the presence of physical dormancy.